(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to identify the relationship between the phosphagenic ability and its contribution to some kinematic variables during the performance of some jumping skills in rhythmic gymnastics.The researcher chose his sample by the intentional method from the students of the second stage in the College of Physical Education for Girls, as the number of the sample was (27) students. Inclination of the torso, angle of flexion in the front and rear leg, angle of inclination of the torso, angular velocity)